Fluids selection and performance analysis of a polygeneration plant with exergy recovery from LNG-regasification. - Atienza-Márquez, Antonio; Bruno, Joan Carles; Akisawa, Atsushi; Nakayama, Masayuki; Coronas, Alberto; Atienza Márquez, Antonio; Bruno, Joan Carles; Akisawa, Atsushi; Nakayama, Masayuki; Coronas, Alberto (Elsevier, 2019)
Liquefied Natural Gas (LNG) is a valuable exergetic source due to its low-temperature (−162 °C). However, LNG is regasified using seawater as heat source and without exergy recovery in most of LNG terminals worldwide. In this paper we model a polygeneration plant that recovers the low-temperature and pressure exergy from LNG-regasification to generate simultaneously power and refrigeration in a District Cooling network at three different temperature levels. The plant is divided into different subsystems arranged in cascade. The objective of this research is the selection of the most suitable working fluids and heat transfer fluids for operating in each subsystem. The performance of the system is analyzed from the thermodynamic and environmental point of view. Although neither of the candidate fluids satisfies all the desirable features, the selected fluids are: methane, carbon dioxide and propane. The plant achieves an equivalent electricity production of 125 kWh for metric ton of LNG regasified with an exergetic efficiency of 40.6%. Besides, the seawater utilized in the plant is 60% lower than the required by the common LNG regasification process and an annual emission of 75 thousand tons of CO2 is avoided.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/16505
Keywords: Gas natural licuado; Gases - Licuefacción; Liquefied natural gas (LNG); LNG regasification; Physical exergy recovery; Polygeneration; Fluids selection